(untitled) (Fiep Bulletin - online, 2014)
The comprehension of the movement of the Man and of his motor development is essential as it constitutes one of the most intrinsically human characteristics.The child passes by the acquisition of several motor marks which characterise each age and that are very important to the parents, as they represent the evolution, even ontological, of the child.At 2004, as a physiotherapist at a certain health institution in the area of Oporto, we were confronted with a child, Maria, who had a rare genetic disease, the Mucolipidosis II, in which the normal motor development is seriously compromised (Lee and McGvern, 2003).The objective of the work is to perceive the "mourning" (Howarth and Leaman, 2001) of the parents facing the "non motor development" of their daughter. So we tried to establish the life history (Poirier et al., 1995) of Maria through interviews not directional to her parents, by registering their testimonies in an audio recorder during the physiotherapy sessions. Apart from the interviews, the information was obtained through the elaboration of a camp diary and the register of the pertinent data taken from the medical reports and our interaction whilst her physiotherapist.The testimonies of Maria’s parents were duly listened to and subjected to an analytical process called analysis of contents (Vala, 1986).From the interpretation of the data we came to the conclusion that the parents have been reconfiguring their expectations concerning the motor development of Maria, each time less demanding, in a kind of resignation by the nearly immobility of the same.